Perbandingan Sistem Pinjaman IMF dan BRICS New Development Bank serta Potensi Dominasi Sistem Moneter Internasional - Pamungkas, Mahendra Lantang; Rahayu, Riswanti Dyah Sekar; Krisyanti, Trieska Ayu (Nation State: Journal of International Studies, 2019)
America is the dominant power for a long time since the World War and gave many aid for many state developments in the world with their ‘Marshall Plan’ policy. America domination clarified by the existence World Trade Organization. United States of America legitimation not only limited to WTO, there are several international economic organizations such as World Bank and International Monetary Fund where the America hold an important power. Countries that want to compete with America legitimacy establish an organization called BRICS. BRICS consist of Brazil, Russia Federation, India, China, and South Africa. BRICS created a bank called BRICS NDB or National Development bank to compete IMF domination. This research will explain the differentiation between IMF and NDB, alongside with how NDB have capability to compete IMF as an international bank that give loans to countries. This research uses descriptive comparative method, so this research will have focused on comparation between the two banks. Analysis on this research will use Structural Power Theory with Middle Power concept to explain IMF domination and how NDB that created by Middle Powered countries can replace IMF domination.